Individual Socialization and Cultural Factors In The Era Of Informatization - Ibragimov Doniyor Bakhtiyor og‘li (Indonesian Journal Publisher, 2026)
This article provides a scholarly analysis of the distinctive features of individual socialization in the era of informatization, as well as the cultural factors influencing this process. The study examines the social transformations that emerge in the course of individuals’ adaptation to society and the internalization of social norms and values under conditions of globalization and the rapid development of information and communication technologies. Language, traditions and customs, religious beliefs, the education system, historical memory, and national values are considered as key cultural determinants of individual socialization. The article also analyzes the interaction between virtual space and the real social environment in an information society, along with their impact on individual identification and the formation of national consciousness. The research findings are of theoretical and practical significance for a deeper understanding of the process of individual socialization and for ensuring social adaptation and cultural stability among the younger generation